Development of Green Economy: Myth or Real Admiration - S. Bobushev , Temirbek (International Journal of Scientific Research and Management (IJSRM), 2023)
It will soon be 10 years since the international community, speaking out about the causes of climate change at the global level, has gradually moved on to the issue of transition to the development of a “green” economy as an acceptable way out of the situation of growing greenhouse gases and carbon dioxide emissions into the atmosphere. However, despite serious contradictions between the capabilities and readiness of countries to transition to a green economy, politicians in a number of developed countries and, above all, the European Union (EU), argue that such a transition is possible in the short term and has even already been accomplished in some countries. as if by default. How should such assurances be accepted - as real anticipations of a process that has not yet taken place, or should the attention of scientists and the public be focused on obvious inconsistencies or obstacles to such a transition? Complications on the discussed path of transition from a market to a “green” economy give rise to many questions that require clear, concise and well-founded answers and solutions.